Computer-based personalized feedback intervention for cigarette smoking and prescription analgesic misuse among persons living with HIV (PLWH). (April 2019) - Ditre, Joseph W.; LaRowe, Lisa R.; Vanable, Peter A.; De Vita, Martin J.; Zvolensky, Michael J.
Abstract: Pain, tobacco cigarette smoking, and prescription opioid misuse are all highly prevalent among persons living with HIV (PLWH). Smoking and pain medication misuse can lead to deleterious outcomes, including more severe pain and physical impairment. However, we are not aware of any interventions that have attempted to address these issues in an integrated manner. Participants ( N = 68) were recruited from an outpatient infectious disease clinic and randomized to either a computer-based personalized feedback intervention (Integrated PFI) that aimed to increase motivation, confidence, and intention to quit smoking, and decrease intentions to misuse prescription analgesic medications, or a Control PFI. Results indicated that PLWH who received the Integrated PFI (vs. Control PFI) evinced greater post-treatment knowledge of interrelations between pain and tobacco smoking. Moreover, participants who received the Integrated PFI and smoked at least 10 cigarettes per day (but not < 10 CPD) reported greater confidence and readiness/intention to quit smoking. Effects of the Integrated PFI on knowledge of pain and opioid misuse, and attitudes/intentions regarding prescription pain medication misuse were not statistically-significant. Taken together, these results indicate that this novel intervention strategy may offer promise for addressing a critical public health need in a population that is generally underrepresented in clinical research. Highlights: A brief PFI was developed to address cigarette smoking and prescription pain medication misuse. The computer-based Integrated PFI content was tailored for older PLWH who were prescribed analgesic medication. The Integrated PFI (vs. Control PFI) resulted in greater knowledge of pain-smoking interrelations. The Integrated PFI also resulted in greater confidence/readiness to quit, but only among heavier smokers. Future research should examine the efficacy of this portable integrated treatment.